A new system for human movement induction based on virtual reality - José Moráguez Piñol; Elías Trenard García; Carlos Díaz Novo (Revista Cubana de Ciencias Informáticas, 2018)
Nowadays there is a variety of new technologies for physical exercising and motor rehabilitation such as: serious games, natural user interfaces, and augmented reality. However, the application of these technologies is insufficient compared to traditional methods. For this reason, this paper discusses the design, implementation and testing of a human movement induction system based on Virtual Reality. The system offers three types of movements: two for the upper limbs, and one for the lower limbs. Each movement can be customized to the subject’s characteristics, in order to develop biomechanical parameters such as speed, and skills such as coordination and balance. The proposed system allows audio-visual feedback, automatic supervision and result analysis; providing service and research support. Compared to similar systems, this design brings innovations such as: the combination of Kinect and Google Cardboard, the indirect measurement of direction and motion speed, and the previsualization of kinematics parameters.